Teoria ograniczeń (Theory of Constraints – TOC) w kontekście wspierania procesu terapii osób jąkających się - Kamińska, Dorota (Logopedia Silesiana, 2017)
Theory of Constraints – TOC in the Context of Stammering Treatment Support The article aims at presenting the practical aspects of the application of TOC (The Theory of Constraints) in the treatment offered to stuttering people. The issues described in the article refer to actions taken within the framework of methodological innovation: “I say what I think” – the TOC method used for training speech fluency and implemented during group therapy activities of stuttering children and youth organized by the Psychological and Pedagogical Clinic in Ciechanów. In her text, the authoress proposes to modify the use of three graphical TOC tools used in support of therapy for stuttering people, namely: the logical branch, the cloud and the ambitious target tree. Key words: stuttering therapy, Theory of Constraints (TOC), support method